(untitled) (Proximus Journal of Sports Science and Physical Education, 2025)
The aim of the study was to design a program based on small games for primary school girls aged (9– 10) years, and to identify the effect of this program on developing some motor abilities among this age group. The research population was intentionally selected from third-grade primary school girls aged (9–10) years, totaling (30) pupils. The research sample was chosen randomly by lottery from the research population and consisted of (15) pupils from the same stage